Three Wheeled Vehicle Dynamics : Static Stability Factor Improvement - LAMHALLI, AYOUB (Journal of Applied Science, Engineering and Technology, 2023)
Three Wheeled Vehicles are gaining popularity across various Asian and African countries. They are characterized for their relatively low susceptibility to rollover when compared to Four Wheeled Vehicles. Establishing an analytical criterion based on architectural parameters such as wheelbase, rear track, masses, and center of gravity coordinates is crucial. This criterion assists manufacturers, particularly during the initial design stages, providing valuable guidance for optimizing vehicle stability. The Static Stability Factor serves as a prominent design criterion in the automotive sector, offering an assessment of a vehicle's resistance to rollover incidents. This paper aims to enhance the existing criterion initially proposed by Huston et al., particularly by addressing scenarios where a load is unevenly distributed on the vehicle's tray. The findings of this study underscore the high sensitivity of such vehicles to unsymmetrical loading configurations.